A differential evolution-based routing algorithm for multi-path environment in mobile ad hoc network. Issue 1 (14th May 2019) - Sharma, Anju; Sinha, Madhavi
Optimisation is a procedure through which the best possible ways of decision variables are obtained under the given set of constraints and in accordance to a selected optimisation objective function. Over the last decade, differential evolution (DE) algorithms have been extensively used in various problem domains and succeeded effectively in finding the optimal solutions. The present paper emphasis on a DE algorithm-based ad hoc on-demand multi-path distance vector (DE_AOMDV) protocol for mobile ad hoc network (MANET). The proposed DE_AOMDV routing protocol has better performance and improves the quality of the MANETs. The main objective of this research paper is to find the optimal path from available multiple paths between source and destination to be used in route recovery process. DE_AOMDV provides backup paths to avoid reroute discovery in the case of link failure between nodes. Simulation based results and data analysis shows DE_AOMDV protocol is better than AOMDV.